2020
DOI: 10.33448/rsd-v9i7.4245
|View full text |Cite
|
Sign up to set email alerts
|

Atividade antiaderente dos óleos essenciais de Eucalyptus globulus e Eucalyptus citriodora contra cepas de Klebsiella pneumoniae

Abstract: The present work aims to evaluate the Minimum Inhibitory Concentration of Adherence (MICA) of the essential oils of Eucalyptus globulus and Eucalyptus citriodora against the bacterium Klebsiella pneumoniae. It was performed the determination of the Minimum Inhibitory Concentration of Adherence (MICA) using the inclined tube technique, in the presence of 5% sucrose. After 24 hours, the reading was performed through visual observation of the bacterium's adherence to the tube walls. It was observed that the essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 16 publications
(11 reference statements)
1
2
0
2
Order By: Relevance
“…However, in the present research, the product being tested in this study was effective in inhibiting the adherence of Escherichia coli. This corroborates the findings of Ramalho et al (2020), who observed that the essential oil of Eucalyptus globulus had an anti-adherent activity of 1:64, showing a positive result at a lower concentration of the oil compared to the result obtained by chlorhexidine digluconate 0.12%, which showed inhibition at a higher concentration of 1:8, confirming that this plant species is also effective in inhibiting biofilm formation against clinical strains of E. coli of human origin.…”
Section: Discussionsupporting
confidence: 90%
“…However, in the present research, the product being tested in this study was effective in inhibiting the adherence of Escherichia coli. This corroborates the findings of Ramalho et al (2020), who observed that the essential oil of Eucalyptus globulus had an anti-adherent activity of 1:64, showing a positive result at a lower concentration of the oil compared to the result obtained by chlorhexidine digluconate 0.12%, which showed inhibition at a higher concentration of 1:8, confirming that this plant species is also effective in inhibiting biofilm formation against clinical strains of E. coli of human origin.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, taking into account the bacterial strain, Ramalho et al (2020), used strains of Klebsiella pneumoniae (kp 102), grown in Mueller Hinton broth in test tubes in order to evaluate the Minimum Inhibitory Concentration of Adherence (MIAC) of the essential oils of Eucalyptus globulus and Eucalyptus citriodora, and as a positive control was employed chlorhexidine digluconate at 0.12%. Thus, when analyzing the results of the anti-adherent activity of the EOs, it was obtained that the EO of Eucalyptus globulus showed good efficiency against biofilm formation by Klebsiella pneumoniae showing results equivalent to the control chlorhexidine digluconate 0.12%, and inhibiting biofilm formation at the same concentration 1:8.…”
Section: Resultsmentioning
confidence: 99%
“…O método da CIMA foi utilizado na presente pesquisa por permitir avaliar o potencial antiaderente dos produtos naturais utilizados no estudo de forma rápida e eficaz. Além disso, outra vantagem desse método se caracteriza pela análise experimental de forma observacional direta, possibilitando a seleção de produtos com potencial antiaderente (RAMALHO et al 2020). Fonte: Autoria própria.…”
Section: Resultsunclassified